Feedback on student engagement in song activity during Spanish online class - Husain, Salina; Darmi, Ramiza; Mohd Nor, Mariyati; Ismail, Radhiah (Human Resource Management Academic Research Society, 2022)
The worldwide advancement of digital technology has witnessed a change in the teaching and learning system supported with the use of internet. As the world is hit with the Covid-19 pandemic, instructors need to adapt to the new norm including in teaching and learning process, meaning from the use of white board to interactive and flexible technology. In this study the element of technology can be seen when this paper will discuss the use of song from the YouTube channel as a medium during an online class. The Self-Determination theory by Ryan and Deci (2000) is applied in the study. The research design of the study is qualitative by analysing the feedback from students on the activity they participated. A total of 22 respondents participated in the study requiring them to answer questions based on a song they had listened to. The objective of the study was to identify the engagement of students in the given activity. In general, it was found that listening to song as an activity can enhance the understanding of the students in learning Spanish.